Modifikasi Cationic Starch dengan Nanosilika sebagai Retention and Drainage Agent Pada Pembuatan Kertas Liner Medium - Edwin K Sijabat; Ajeng Nimatul Hidayah; Marjanu Priambodo (JURNAL VOKASI TEKNOLOGI INDUSTRI (JVTI), 2022)
Nanotechnology has attracted the interest of many scientists because the changes in physical properties occurred at the size of 1-100 nm in the form of vast surface area, high mechanical strength, and high porosity. Silica is an element with high uses in various fields such as biotechnology. Silica nanoparticles are silica made on a nanoscale whose use is increasing. Nanosilica is widely used in the industry as a retention and drainage aid, usually associated with cationic polyelectrolytes such as cationic starch. The use of nanosilica in the paper-making process aims to improve the dewatering process and the retention of fine particles such as fines. Retention is one of the important parameters at the wet-end stage because it affects the ability of the additive to be retained on the fiber to the sewage treatment system. However, retention also has a negative impact on the dewatering rate and the physical properties of the paper produced, so that it is often neglected in the industry because it reduces runability in the paper-making system. This research was conducted to determine the effect of modifying cationic starch with nanosilica on retention, drainage rate, and paper properties. In this research, nanosilica was synthesized by using sol gel method, and the synthesis results indicate the presence of a nanosilica functional group and nanosilica at the size of 46-86 nm. In addition, modifying cationic starch with nanosilica with variations of 0.5% and 1% cationic starch and 0.5%, 1% and 1.5% nanosilica. The results obtained indicate that the optimum dose of nanosilica for each of the corresponding cationic starch dose, namely to increase retention and drainage for 0.5% cationic starch, the optimum use of nanosilica is 1% with a retention value of 90% and drainage value of 445 ml, for 1% cationic starch, the optimum use of nanosilica is 0.5% with a retention value of 89.8% with the optimum drainage value of 0% nanosilica and drainage value of 440 ml. In addition to wet-end testing, the sheet properties testing was also conducted to determine the effect of retention due to modification of cationic starch with nanosilica on the sheet physical properties. The test results indicate that the addition of nanosilica to the wet-end system has a positive impact on sheet properties.